Solid-state electron-mediated z-scheme heterostructured semiconductor nanomaterials induce dual programmed cell death for melanoma therapy - Yiping Ren; Yun Wang; Cheng Chen; Xiang Yan; Minghao Chao; Yuting Li; Dehong Yu; Yuqi Huang; Xiaoyang Hou; Fenglei Gao; Guan Jiang; Ming Guan (Journal of Nanobiotechnology, 2024)
Abstract The programmed cell death (PCD) pathway removes functionally insignificant, infection-prone, or potentially tumorigenic cells, underscoring its important role in maintaining the stability of the internal environment and warding off cancer and a host of other diseases. PCD includes various forms, such as apoptosis, copper death, iron death, and cellular pyroptosis. However, emerging solid-state electron-mediated Z-scheme heterostructured semiconductor nanomaterials with high electron-hole (e–h+) separation as a new method for inducing PCD have not been well studied. We synthesize the Bi2S3-Bi2O3-Au-PEG nanorods (BB-A-P NRs) Z-scheme heterostructured semiconductor has a higher redox capacity and biocompatibility. Firstly, the BB-A-P NRs are excited by near-infrared (NIR) light, which mimics the action of catalase by supplying oxygen (O2) and converting it to a single-linear state of oxygen (1O2) via e–h+ transfer. Secondly, they react with hydrogen peroxide (H2O2) and water (H2O) in tumor to produce hydroxyl radicals (•OH), inducing apoptosis. Intriguingly, the Caspase-1/Gasdermin D (GSDMD)-dependent conventional pyroptosis pathway induced cellular pyroptosis activated by apoptosis and reactive oxygen species (ROS) which causes the intense release of damage associated molecular patterns (DAMPs), leading to the inflammatory death of tumor cells. This, in turn, activates the immunological environment to achieve immunogenic cell death (ICD). BB-A-P enables computed tomography imaging, which allows for visualization of the treatment. BB-A-P activated dual PCD can be viewed as an effective mode of cell death that coordinates the intracellular environment, and the various pathways are interrelated and mutually reinforcing which shows promising therapeutic effects and provides a new strategy for eliminating anoxic tumors. Graphical abstract